1042. Stenotrophomans maltophilia Bacteremia, A 10-Year Tertiary Center Experience. (26th November 2018) - Hamdi, Ahmed; Fida, Madiha; AbuSaleh, Omar; Beam, Elena
Abstract: Background: Stenotrophomonas maltophilia is a hospital acquired infection that is associated with high morbidity and mortality. There has been a reported rise in S. maltophilia infections, presumed secondary to the increase in the population at risk. Methods: We retrospectively reviewed all hospitalized adult patients in Mayo Clinic, MN with S. maltophilia bacteremia from January 2008 through January 2018. We analyzed patient population and described patients at risk, sources of infection, and changes in antimicrobial susceptibility profile. Results: A total of 94 patients were analyzed, including 52 males, median age of 56 (46–65.75 IQR). The population included 60 infections in those with malignancies and 30 infections in transplant recipients. At presentation, 58 (61.7%) were febrile, while 54 (58.1%) presented with hemodynamic instability. Majority (70.2%) received broad-spectrum antimicrobials within 2 weeks of presentation. The most common source was catheter associated infection ( n = 60), 15 cases were secondary to gastrointestinal, and 9 due to a pulmonary source. Almost half, 46 (48.9%) required ICU admission. Two patients were diagnosed with endocarditis. Most isolates, 61(64.9%), were resistant to ceftazidime, 2 (2.2%) resistant to TMP/SMX and 20 (21.5%) were resistant to levofloxacin. Exposure to a quinolone in the 30 days prior to presentation did not impact fluoroquinolone resistance. Five patients were exposed to Trimethoprim/Sulfamethoxazole (TMP/SMX) in the 30 days prior to presentation, which was associated with higher rate of TMP/SMX resistance compared with those without exposure (80% vs. 98.8%, P = 0.004). Treatment options commonly included combination therapy, and TMP/SMX was a primary agent used in the majority, 59 (62.8%). All-cause in-hospital mortality was 26.6%. All-cause mortality was lower for line associated infections (16.67%) vs. other sources (44.12%) with P = 0.0038. Conclusion: S. maltophilia bacteremia should be considered in hospitalized patients with recent use of broad-spectrum antibiotics. Although TMP/SMX continues to have reliable activity, use of empiric ceftazidime pending susceptibility testing should be avoided as trend toward increasing resistance is noted. We noted a drop in TMP/SMX susceptibility in those with recent reported TMP/SMX use. Disclosures: All authors: No reported disclosures.